Identifikasi Potensi Desa Tawaang Timur Sebagai Salah Satu Daya Tarik Wisata di Minahasa Selatan - Pearl Loesye Wenas (PolimdoSains, 2021)
The development of the province of North Sulawesi, specifically South Minahasa, especiallyEast Tawaang Village, has a very interesting potential to be developed into a rural touristdestination. However, to develop these destinations, it is necessary to identify what potentialscan become the backbone of the area. Determining the identification of potential in the area willfacilitate the initial steps for strategy preparation and initial mapping as one of the leadingdestinations in South Minahasa.Qualitative descriptive research method is used to determine the potential that exists in thevillage of East Tawaang and is supported by interviews of related people to get valid results. Theresults of this research show that the village of Tawaang Timur has various potentials that can bedeveloped.By formulating a SWOT analysis, it can be found that the strengths of East Tawaang Villageinclude the potential for natural tourism, culture and local arts. Natural tourism such as moinitbeach, songkur beach, mangrove forest, BTO dam has natural tourist attractions. Art tourismwhich is the basis of the Minahasa art, such as the kebesaran dance, lenso, and the culture ofmaking traditional cap tikus needs to be a concern. weakness of East tawaang Village in terms ofinfrastructure and human resources.From the village profile, there are still many people who have very low education, infrastructureto get to tourist attractions is still lacking, roads that are still damaged or not even paved, publictoilets are not available, restaurants or eating places that have not been formed and properlyorganized, service and cleanliness which is very minimal, lodging, souvenir shops that are notyet available must be a priority that need fixing. The involvement of the local government andlocal communities is very lacking in understanding the tourism potential in the village of EastTawaang. There are many opportunities for East Tawaang Village, the potential for nature, artsand culture should be able to be explored deeper and be prepared more thoroughly to become atourist village because this village has potentials that are very rarely found in other villages,traditional arts need to be formed and traditionalized to children - Adolescents and young people,dance studios are made to shape the character of the citizens' arts and culture, and can bedisplayed in front of tourists visiting potential places, training on handicrafts to make souvenirobjects that can be used as a driving force for the tourism economy. The village of TawaangTimur has threats from other villages if they are late or do not think that the tourism sector is amainstay of the village, in addition to the threat of competition, the threat of local cultural threatsthat are degraded due to technological developments can be lostKeywords: Identification, Potential, Tourist Attraction